Pengembangan Aplikasi Mobile Pengingat Jadwal Layanan Posyandu dengan Menggunakan Teknologi Firebase Cloud (Studi Kasus : Posyandu Raflessia Kelurahan Tanjungsekar, Kecamatan Lowokwaru Kota Malang) - Velient Vinandha; Bayu Priyambadha; Heru Nurwarsito (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Posyandu is health services program where it facilitated by government to community, however the program is from goverment, posyandu held by community to comunnity. Although this program held by community, the Ministry of Health also has a role in overseeing and supporting every activity in the posyandu both technically and financially. Posyandu offers the community so many services such as Basic Health Service for mother and child, Family Planning Service, Immunization for Kids and Infants, Information of aNutrition Delivery Service, and Diarrhea Prevention and Treatment Service. All of the services are written on a pocket book that happens to be the health guidance. But information in the form of a book still has some boundaries in its usage. We often forget where we put the book or even it gets lost. So that the author is currently doing a research of developing an application that may help record the process of administration recording of Posyandu's services and remember the Posyandu's activity schedule, by recording administration of posyandu service in an application that can help the community to obtain information about posyandu services and remember schedules of the posyandu. This application is developed using Java programming language and using firebase database technology to save data of the application. Firebase is the newes of technology by Google that can be use to many platform one of many of the platform is mobile. So this application can remind the user to be able to remember posyandu activities according to the existing schedule. This application can be developed based on design program. This application already tested using some software testing, that is unit testing, integration testing and validation testing. This application can be used easily, based on testing that has been done using usability testing, that get 83,5 score of SUS, this score is classified to the acceptable category.